Photonic Crystal Assisted L-Shaped Waveguide Bend - Şengün, Hediye Duygu; Sözüer, Hüseyin Sami (Izmir Institute of Technology, 2009)
Photonic crystals are periodic dielectric structures. This periodicity allow us to manipulate light in ways that have not been possible before. As a result, photonic crystal waveguide components play a significant role in integrated optical circuit design because waveguides allow only certain electromagnetic wave modes to propagate inside the structure. There are many corresponding applications that rely on total internal reflection. However, with total internal reflection, there is a problem in guiding light through sharp corners, large optical losses occur around tight curves with a small bending radius. A simple explanation for these losses is that the angle of the incident light too low for total internal reflection when wave turns through a sharp corner. Thus, an unacceptable fraction of the electromagnetic energy is radiated out of the waveguide. To overcome this difficulty, in this thesis, we demonstrate a novel method for guiding light through sharp corners, using a 1 photonic crystal slab waveguide for the straight sections, and assisted by 2D Line Defect Waveguide at the corners.Plane Wave Method and Supercell Method are used to Figure out parameters and obtain the guided mode for our proposed structure. Then, numerical simulations (FDTD) reveal nearly perfect transmission at certain frequency ranges. Also, in this thesis different corner elements are used to show highly efficient transmission of light through sharp corners. Thus, light can be guided through a 90. corner, almost without loss, by using different corner elements. "Crystals are like people, it is the defect in them which tend do make them interesting". Colin Humphreys.
Thesis (Master)--Izmir Institute of Technology, Physics, Izmir, 2009
Includes bibliographical references (leaves: 79-82)
Text in English; Abstract: Turkish and English
xv, 88 leaves
Keywords: QC793.5.P42 .S47 2009; Photons; Photonic crystals; Wave guides